PENGARUH EKSTRAK KULIT BATANG Rhizophora apiculata TERHADAP KADAR GLUKOSA DARAH Rattus norvegicus YANG DIINDUKSI DEKSAMETASON - NABILA LARASATI, ARLISA; HANDAJANI, FITRI; PUTRO, SAPTONO; KOMALASARI, INTAN (Hang Tuah Medical Journal, 2026)
Background: Dexamethasone is a glucocorticoid, if used long term it can cause increased oxidative stress and hyperglycemia. In diabetes patients, large amounts of antioxidants are needed as an antidote to free radicals in the body. Ethanol extract of Rhizophora apiculata stem bark has antioxidant and antidiabetic activity. Objective: This study aims to evaluate the effect of ethanol extract of Rhizophora apiculata bark on the blood glucose levels of white rats induced by dexamethasone. Methods: This research use 32 rats grouped into 4 groups. G (-), standard feed, G (+) induced by dexamethasone, GP 1 bark extraxt and induced by dexamethasone at the same time as giving mangrove bark extract, and DT 2, dexamethasone and mangrove bark extract, then on the 22nd day a blood sample was taken to measure blood glucose levels. Results: the average blood glucose level G- = 146.5; G+= 213.375; GP = 185.875; GT = 244.375. In the One Way Anova parametric test, significant results were obtained, 0.015 (p<0.05). Then in the Post Hoc LSD test; G- and G+ had a significance of 0.028 (p<0.05), while the G+ and GP and GT groups did not show significant differences. Conclusion: Subcutaneous dexamethasone induction treatment was proven to increase blood glucose levels in male Rattus norvegicus. Administration of ethanol extract of Rhizophora apiculata stem bark as prophylaxis or therapy was unable to reduce blood glucose levels of male Rattus norvegicus induced by dexamethasone.